PENGARUH UKURAN PERUSAHAAN, CORPORATE GOVERNANCE DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di Bursa Efek Indonesia periode 2011 – 2014) - RIANA RIANA; DIAH ISKANDAR (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
This research aim to know the influence of partially and simultaneously of the size of company, institutional ownership, board of director, independent commissioner, audit committee, and capital structure against the value of company. The object of this research is the Indonesian mining company listed on the Indonesia Stock Exchange during the period 2011-2014 . This study was conducted on 22 companies by using quantitative approach diskiptif .Therefore, the analysis of the data used is the statistical analysis in the form of multiple linear regression test. These results indicate that in partial sized companies and institutional ownership affect the value of the company, while the board of directors, independent directors, audit committee, and capital structure does not affect the value of the company. While simultaneously the variable size of the firm, Institutional Ownership, Board of Directors, Commissioners Independen, the Audit Committee, and Capital Structure effect on firm value. This is evidenced from the results of simultaneous test (F test) and the results of the partial test (t test) also shows the value of the six independent variables that support the hypothesis.